Socio-Philosophical Basis of Strengthening Values in Family Relations (Zien Journal of Social Sciences and Humanities, 2024)
As in many nations of the world, the Uzbek people's relations between family members are distinguished by their moral and axiological aspects. Such family relations are considered the first great treasure in the process of realizing the national identity of each nation. For several thousand years, the cultural values and spiritual heritage of the Uzbek people have served as a powerful source of spirituality for the people of the East, as well as the people of the whole world. In recent years, fundamental national and ideological changes have begun to take place in the spiritual life of the Uzbek people. We had the opportunity to objectively study our valuable scientific and spiritual heritage created by our ancestors long ago